Investigating the Effect of Three Antigens of Citrobacter freundii on Rabbit’s Immune Response - Mohammed, Roua J; Al-Samarraae, Ikram Abbas A (The Iraqi Journal of Veterinary Medicine, 2021)
Citrobacter freundii (C. freundii) is responsible for a number of significant opportunistic infections. The present research was aimed to estimate the immune response of rabbits immunized with whole cell sonicated antigen (WCSA), lipopolysaccharide (LPS), and DNA antigens (Ag) extracted from C. freundii. Twenty-four Albino rabbits of both sexes, with 2-3 kg body weight, were divided randomly into four groups (6 rabbits for each). Two types of tests were performed including ELISA and skin test (delayed type hypersensitivity, DTH)). The 1st group was immunized with WCSA (1000 μg/mL). The 2nd group was immunized with LPS Ag at the same dose. The 3rd group was immunized with DNA extracted Ag (0.083 μg/mL). The 4th group (negative control) was injected with 1 mL PBS (pH 7.2) subcutaneously. After 14 days, rabbits were given booster doses of same Ag. The immunized animals showed significant increase of IgG and IL-6 concentration (P<0.05) following 28, 32, 46, 50 and 60 days of immunization in comparison with the negative control group. Concerning DTH, it showed an increase in the means of induration and erythema, with significant differences (P˂0.05) exerted by the concentrated antigens in all immunized groups after 24 h and 48 h compared with diluted Ag and negative control group. In conclusion, WCSA and LPS Ag, in comparison to DNA Ag, were observed to promote stronger humoral (IgG) and cellular (DTH and IL-6) immune responses. DNA Ag, on the other hand, elicited a weaker humoral and cellular immune response than other Ag.